2021
DOI: 10.1186/s12968-021-00752-1
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, multi-morbidity and genetic impact on myocardial involvement and its recovery from COVID-19: protocol design of COVID-HEART—a UK, multicentre, observational study

Abstract: Background Although coronavirus disease 2019 (COVID-19) is primarily a respiratory illness, myocardial injury is increasingly reported and associated with adverse outcomes. However, the pathophysiology, extent of myocardial injury and clinical significance remains unclear. Methods COVID-HEART is a UK, multicentre, prospective, observational, longitudinal cohort study of patients with confirmed COVID-19 and elevated troponin (sex-specific > 99th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Troponin elevation was not an eligibility criterion, and renal dysfunction was not an exclusion criterion. Our study design stands apart from previous studies that involved selected populations (COVID-HEART 35 and COVIDsortium 36 ), retrospective case selection 19 , 20 or a sample size limiting generalizable conclusions 12 . In a cardiac screening study of 789 North American professional athletes who had tested positive for COVID-19, cardiac abnormalities were uncommon (3.8%) and myo-pericarditis was identified in 0.6% of individuals, without adverse cardiac events 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Troponin elevation was not an eligibility criterion, and renal dysfunction was not an exclusion criterion. Our study design stands apart from previous studies that involved selected populations (COVID-HEART 35 and COVIDsortium 36 ), retrospective case selection 19 , 20 or a sample size limiting generalizable conclusions 12 . In a cardiac screening study of 789 North American professional athletes who had tested positive for COVID-19, cardiac abnormalities were uncommon (3.8%) and myo-pericarditis was identified in 0.6% of individuals, without adverse cardiac events 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The true long-term cardiovascular outcome after COVID-19 should preferably be assessed with prospective, observational, longitudinal cohort studies. An excellent example is the COVID-HEART study which is a multi-center study including patients with confirmed COVID-19 and elevated troponin levels [23] . Baseline assessment in the COVID-HEART study will include cardiac magnetic resonance imaging, serial ECG, biomarkers, genetics and quality of life assessment.…”
Section: Discussionmentioning
confidence: 99%
“…He underwent cardiovascular magnetic resonance (CMR) imaging as part of a UK, multicentre, Urgent Public Health research study (ISRCTN58667920). 1 CMR revealed mild impairment in left ventricular ejection fraction (LVEF 45%).Stress perfusion CMR revealed no inducible ischaemia, whereas late gadolinium enhancement images showed patchy mid-wall hyperenhancement consistent with COVID-19 myocarditis ( figure 1A ). T1-mapping confirmed myocardial injury in a non-ischaemic pattern ( figure 1B ) and global myocardial T2 was also elevated consistent with acute inflammation ( figure 1C ).…”
Section: Descriptionmentioning
confidence: 99%